Father Roles in Islamic Perspective on Islamic Senior High School in Jakarta - Bunyanul - Arifin; Endin - Mujahidin; Zainal Abidin Arief (Journal of Child Development Studies, 2017)
The previous study showed that the quality of father-child relationship could predict the quality of family relationship. Father involvement were positively affecting child development. This study aimed to identify father roles on children in Islamic perspective. The study was conducted in Islamic Senior High School in West Jakarta. Five hundreds student from class IX were used in this study, and selected by using cluster random sampling method. Data were collected using in-depth interview and self-report with questionnaire as the tools. Father roles consist of six dimensions: (1) leader, (2) economic provider, (3) protector, (4) educator, (5) playmates, and (6) friend. This study found that father’s role as a leader, economic provider, and protector were the roles that most felt by children. Meanwhile, father’s role as an educator, playmates, and friend were the roles that less felt by children. Based on the result of the study, it is important to provide parenting education programs (training, seminars, and counseling) for parents especially father to enhance father roles in child live